Perilaku Konsumsi Masyarakat Modern Perspektif Islam: Telaah Pemikiran Imam Al-Ghazali dalam Ihya’ Ulumuddin - Elvan Syaputra (Falah: Jurnal Ekonomi Syariah, 2017)
Satisfaction in fulfilling what someone want to consume is the measure of happiness. Such shopping now becomes an endless human need. Herein lies the consumption in the sense of altering “consumption as necessary” into “consumption as wants”. In this case, it is intended that one’s motivation for spending is no longer to meet basic human needs, but rather to relate to their identity. This proves that the culture of consumerism has changed the pattern of people’s dependence in consume. This study aims to conduct an in-depth analysis of the pattern of consumption of modern society in terms of Islam; especially Imam al-Ghazali in Ihya ‘Ulumuddin. The conclusion of this study is that Al-Ghazali laid the foundation of a Muslim's life by attaining the goal of the salvation of the hereafter. As for one way to achieve the purpose of the Hereafter by running the consumption activity based on Islamic sharia.